One-year follow-up of clinical and morphological outcomes in elite athletes with early-stage lower extremity tendinopathy - Seidler, M.; Svensson, R.; Meulengracht, C.; Christensen, K.; Brushøj, C.; Kracht, M.; Hjortshoej, M.; Magnusson, S.; Bahr, R.; Kjær, M.; Couppé, C. (European Journal of Sport Science, 2025)
Little is known about early tendinopathy in elite athletes. This study aimed to investigate changes in clinical and ultrasonography outcomes over 1 year and assess the prognostic values of these outcomes at baseline with respect to tendinopathy progression. Sixty-two elite athletes (24 ± 5 years) with early phase (symptom duration < three months) Achilles or patellar tendinopathy (AT and PT) were examined at baseline and after one year. Pain-guided activity modification was the only intervention. Clinical outcomes were assessed using Victorian Institute of Sports Assessment questionnaires (VISA) for function and symptoms, pain scores (1-10 numerical rating scale (NRS)) and ultrasound tendon morphology (thickness, echogenicity and power Doppler (PD) flow area). A linear mixed-effects model analysed changes from baseline to 1 year. Athletes showed clinical improvements in VISA-Achilles (baseline: 66 ± 5 vs. one-year: 87 ± 2, 95% CI: 13-30, p < 0.0001 and effect size d = 3.8), VISA-Patella (baseline: 69 ± 3 vs. one-year: 86 ± 1, 95% CI: 10-26, p < 0.0001 and effect size d = 3.6) scores and most NRS pain scores (= 2 points). Tendinopathic Achilles tendons' peritendinous thickness was reduced (-0.79 mm, p = 0.0188 and effect size d = 0.5), whereas patellar tendons remained enlarged. For both AT and PT, lower baseline PD was associated with a greater reduction in thickness over time (p < 0.001) and higher baseline VISA scores were linked to greater increases in echo intensity over time (p = 0.0363). In conclusion, elite athletes with early phase AT and PT showed clinical improvement over 1 year, with morphological changes in tendinopathic Achilles tendons only. Lower baseline PD and better initial VISA scores represent a better prognosis for tendinopathy morphology and symptoms.